Perencanaan Pengurus Nasyiatul Aisyiyah Kota Medan Dalam Sosialisasi Kesehatan Reproduksi Pada Remaja - Popyanti, Dila; Samosir, Hasrat Efendi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This study aims to analyze the planning carried out by the Medan City Nasyiatul Aisyiyah Board in providing reproductive health socialization to adolescents. Using a qualitative method, this research explores the program planning that will be implemented. The data collection techniques used were observation, interview, literature study and documentation. The results showed that the Board of Nasyiatul Aisyiyah Medan City has planned a socialization program on the importance of reproductive health in adolescents. The planning includes seminars, health checks, health counseling, collaborating with RSU Muhammadiyah North Sumatra, conducting cadre training and utilizing digital media. This can have a positive impact in improving adolescents' understanding of reproductive health, although it still faces challenges in reaching adolescents as the main target. In this case, innovation in delivery methods is needed so that this socialization is more effective and acceptable to the youth.